Parental Child Abduction In Indonesia: A Criminal Law Perspective - Sofian, Ahmad; Yulia, Rena; Hendra, Rio; Setyawati, Melly; Capaldi, Mark P (Journal of Indonesian Legal Studies, 2025)
This research examines parental conflicts that lead to "child abduction" within families and the criminal law aspects in Indonesia, including its differences from virtual child abduction.  It employed the normative method, utilizing a legal framework focusing on criminal law and child protection legislation. Comparative legal approaches were also utilized in the research. The novelty of this study lies in its exploration of resolutions through criminal law for parents who abduct their children without the consent of the other parent. The wrongful actions of a parent who abducts a child without consent include separating the child, restricting access to the other parent, and disrupting the child's normal development. Within the realm of criminal law, this act by a parent is not considered a criminal offense. Consequently, it cannot be reported to the police, and thus, the police cannot process such abduction reports. This leads to injustice, particularly when the abducting parent prevents the other parent from seeing their biological child. Ultimately, the best interests of the child are no longer prioritized and tend to be neglected. Additionally, in relation to child abduction, perpetrators also utilize digital technology to influence the child. The Indonesian law seems to have failed to protect children from wrongful actions or forced separation from their parents. Therefore, reforms in criminal law related to child protection are needed, particularly concerning cases where a parent abducts their child and separates them from the other parent.